A Psychological Study of Relationship between Dysfunctional Attitude and Self-Esteem in Committing Suicide - Jarchi, Reza; Mostafa Shahiditabar; Servat Shahiditabar (European Journal of Social Science Education and Research, 2014)
Suicide is the act or an instance of taking one’s own life voluntarily and intentionally especially by a person who has no aim to continue his/her life. This study is concerned with the case of suicide who wanted to kill herself by means of a bowl of liquid (combination of pesticide, oil and some drugs) with the symptom of low self-esteem. in the case of methodology, The Dysfunctional Attitude Scale (DAS) is used to measure the attitude of the subject. Coopersmith Self-Esteem Inventory is also used for measurement of self-esteem of the subject. Also some interviews were conducted with the subjects’ school teachers and family. The results of the study show that the subject has low self–esteem and her cognitive misunderstandings are higher than normal. This study also confirms that high cognitive misunderstandings as well as low self-esteem causes suicide.